Gastrocnemius pedicled muscle flap for knee and upper tibia soft tissue reconstruction. A useful tool for the orthopaedic surgeon. Issue 12 (December 2021) - Gkiatas, Ioannis; Korompilia, Maria; Kostas-Agnantis, Ioannis; Tsirigkakis, Spyridon E; Stavraki, Marianna; Korompilias, Anastasios
Highlights: Gastrocnemius flap (medial and lateral heads) consist a reliable option for the coverage of soft tissue defects around the knee joint. The good caliber pedicle, the absence of microvascular anastomosis, and the combination with other regional flaps are some of its advantages. Orthopaedic surgeons with the appropriate training can successfully perform the pedicled gastrocnemius muscle flap transfer. Abstract: Soft tissue defect coverage has always been a challenge for the orthopaedic surgeon. Over the last decades the surgery of flaps has completely changed the prognosis for large defects. The purpose of this study is to retrospectively review our experience with the gastrocnemius muscle as pedicled local flaps for reconstruction of knee and upper third of the tibia soft tissue defects. Twenty-seven patients underwent reconstruction of soft tissue defects around the knee using pedicled gastrocnemius muscle flaps. There were eighteen men and nine women ranged in with a mean age of 50.3 years. Medial gastrocnemius was used in 21 cases, and lateral gastrocnemius in 5 cases. In one patient, soleus and medial gastrocnemius were transferred simultaneously. All but one had at the same time split thickness skin graft for coverage of the muscle. All muscle flaps transferred were successful. There were no complications and all flaps survived completely without vascular compromise, satisfactory coverage of the defect, and good primary wound healing. There has been no recurrence of osteomyelitis. The donor sites healed perfectly with no remarkable resultant functional disability. A mean follow-up of 4.4 years revealed acceptable cosmetic results with high patient satisfaction. Our results indicate that the gastrocnemius muscle transfer is a useful technique for coverage of soft tissue defects in the upper tibia and around the knee in our orthopaedic practice. It is a reliable option for the coverage of exposed bone, the filling up of deep cavities and the treatment of bone infection. The principal advantage of a muscle flap is to bring a real blood supply to the recipient site and to improve the trophicity of the surrounding tissues. The pedicled muscle flap is our preference for the management of soft tissue defects around the knee, when no other procedure, apart from free flap is suitable. The pedicle flap is easier, quicker and with less complications than a free flap. Orthopaedic surgery has gained much from the use of island flap, however, it requires knowledge of the vascular anatomy and its variations promoted through cadaveric dissections and flap dissection courses.